The charter of a municipality’s auxiliary unit – formal issues (Discourse of Law and Administration, 2021)
According to the will of the legislator the organization and scope of operation of a municipality’s auxiliary unit determines the borough’s council. The procedure for adopting this act includes the involvement of the inhabitants in the form of consultations. The article presents the analysis of the charter of a municipality’s auxiliary unit in terms of formal issues. In particular, the passing of the statute of the auxiliary unit as an element of creating such a unit is presented. It is also pointed that it must be proceeded by consultations with inhabitants. The issues of the legal nature, the form, the promulgation as well as distinctiveness of the unit’s statute required by the law are discussed. The considerations are based on judicature, ideas elaborated on doctrines and the author’s findings.
Keywords: Statute of the auxiliary unit borough; form; legal nature; distinctiveness; promulgation